Evaluation and Comparative Correlation of Abdominal Fat Related Parameters in Obese and Non-obese Groups Using Computed Tomography - Raghu Teja, Kompalli J. Satya Siva; Durgaprasad, Bhamidipaty K.; Vijayalakshmi, Payala (Current Medical Imaging, 2021)
Background: Obesity is a significant risk factor for cardiovascular (CV) disease. Abdominal fat is composed of abdominal subcutaneous fat and intra-abdominal (visceral) fat. Computed tomography (CT) is considered one of the most accurate and reliable methods for assessing abdominal fat. Introduction: The present study was based on evaluating abdominal fat by computed tomography and the determination of association between CT obtained abdominal fat volumes, anthropometric indices, and lipid profile. Methods: The prospective study was carried out on 120 subjects referred to the Radiology department for a CT scan. Non - contrast CT scan was performed with 5 mm slice thickness. Abdominal fat volumes were recorded by using CT attenuation values (- 250 to -50 HU). The section was selected at the level of the umbilicus (L4-L5). Intra-abdominal fat and subcutaneous fat volumes were calculated. Body Mass Index (BMI) and lipid profile were recorded for each subject. A comparative study of the CT values, BMI, and lipid profile was undertaken. Results: In the present study, by comparing the anthropometric parameters, CT findings, and lipid profile and blood parameters of the obese and non-obese groups by sex revealed significant sex differences in all the parameters under study. It was also found that the obese male and female groups showed a high prevalence of diabetes, Non-Alcoholic fatty liver disease (NAFLD), and hypertension than non-obese groups. This finding also adds to the chances of getting cardiovascular diseases, specifically in obese individuals. The results found that in obese males and females the abdominal fat-related parameters Visceral fatty acid (VFA) and subcutaneous fatty acid (SFA) showed highly significant relation to anthropometric parameters like BMI, waist circumference (WC) and waist/hip (W/H) ratio on the other hand blood parameters high-density lipoprotein (HDL), low-density lipoprotein (LDL), very-low-density lipoprotein (VLDL), total cholesterol and triglycerides to some extent have a significant relation to abdominal fat-related parameters. In non-obese groups, by studying the influence of anthropometric parameters on abdominal fat-related parameters, it was revealed that WC was strongly affected by the VFA in both sexes. In obese females, more fat was accumulated in the VFA and SFA and for obese males in SFA and for non-obese males in total fatty acid (TFA). Conclusion: Computed tomography assessed visceral fat area remains the most sensitive independent predictor of cardiovascular risk.
Keywords: obesity